Analisis Kinerja Keuangan Pada Perusahaan Daerah Air Minum Wair Pu’an Maumere - Kristina Yulliastri Manona; Andreas Rengga; Kristiana Reinildis Aek (Universitas Nusa Nipa Maumere, 2022)
This study aimed to determine the financial performance of Wair Pu’an Maumere Regional Water Supply Compani based on the Decree of the Minister of Home Affairs Number 47 0f 1999 which is located at jl. Anggur No. 2 Kota Baru, Alok Timur sub-district, Sikka Regency, East Nusa Tenggara.Analysis was carried out using 10 financial ratio indicators based on Minister of Home Affairs no.47. the date used were financial statements in the form of balance sheets, profit and loss, and collection accounts for the Wair Pu’an Maumere Regional Water Supply Company for 2016-2022.The results showed that the success rate of the performance of the Wair Pu’an Maumere Ragional Water Supplay Company based on the Decree of the Minister of Home affairs Number 47 of 1999 during the study, namely 2016-2022 the performance of the Wair Pu’an Maumere Regional Water Supply Company was in the “less” category with a score of 18,75 (2016) and “adequate” with performance scores of of 24,75 (2017), 24,75 (2018), 24,75 (2019), 21 (2020), 20,25 (2021) and 21 (2022).